The interplay of virtualisation, work design, and business process management: A mixed-methods study - Luke Bartlett; Muhammad Ashad Kabir; Jun Han (International Journal of Information Management Data Insights)
Business Process Management (BPM) has emerged as a fundamental aspect of modern business, revolutionising task execution and operational efficiency. This study explored the relationship between virtualisation and work design as well as their impact on BPM system design. An experiment was established where two simulated BPM systems were given to users to operate, one taking advantage of virtualisation and work design, the other not. A mixed method approach involving both quantitative and qualitative approaches was applied to system and usage data collected from these systems as well as a user survey. The analysis illustrates the potential significance of integrating virtualisation and work design in BPM systems. We provide a reflective discussion linking theoretical understanding with empirical evidence. We found that both components not only enhanced the performance and effectiveness of BPM systems, but also improved flexibility, scalability, and user experience. The data supports that a relationship between virtualised resources and work design exists when incorporated into BPM system design. Further, it provides valuable insights into how these elements interact and impact each other. The findings in this study contribute to building a case that establishes the effect of virtualisation and work design on the usability of BPM systems. These findings have very real practical applications that can be applied to existing BPM systems as well as the architecture of future systems. A number of the recommendations made as a result of this research have been applied to commercially available BPM systems.